The expert advantage in dynamic pattern recall persists across both attended and unattended display elements - Gorman, A. D.; Abernethy, B.; Farrow, D. (Attention, Perception, & Psychophysics, 2013)
We examined how differences in attention influence how expert and novice basketball players encode into memory the specific structural information contained within patterns of play from their sport. Our participants were primed during a typical recall task to focus attention on either attacking or defending player formations before being asked to recall the attended or unattended portion of the pattern. Adherence to the instructional set was confirmed through an analysis of gaze distributions. Recall performance was superior for the experts relative to the novices across both the attended and unattended attacking and defensive pattern structures. Expert recall of attacker positions was unchanged with and without attention, whereas recall accuracy for the positions of defenders diminished without attention, as did the novices` recall of both attack and defense formations. The findings suggest that experienced performers are better than novices at encoding the elements from a complex and dynamic pattern in the absence of focused attention, with this advantage being especially evident in relation to the recall of attacking structure. Some revision of long-term memory theories of expertise will be necessary to accommodate these findings